The Inhibition of Monoamine Oxidase by 8-(2-Phenoxyethoxy)Caffeine Analogues - Strydom, B.; Bergh, J. J.; Petzer, J. P. (Arzneimittelforschung, 2012)
Previous studies have documented that substituted 8-oxycaffeines act as inhibitors of human monoamine oxidase (MAO) B. A particularly potent inhibitor among the reported compounds was 8-(2-phenoxyethoxy)caffeine with an IC50 value of 0.383 µM towards MAO-B. In an attempt to improve on the inhibition potency of this compound and to discover highly potent reversible MAO-B inhibitors, in the present study, a series of 8-(2-phenoxyethoxy)caffeine analogues containing various substituents on C4 of the phenoxy ring, were synthesized and evaluated as inhibitors of human MAO-A and -B. The results show that the 8-(2-phenoxyethoxy)caffeine analogues are selective and reversible MAO-B inhibitors with the most potent homologue, 8-{2-[4-(trifluoromethyl)phenoxy]ethoxy}caffeine, exhibiting an IC50 value of 0.061 μM. These highly potent inhibitors are useful leads in the design of therapies for neurodegenerative disorders such as Parkinson’s disease.
Keywords: monoamine oxidase; caffeine; 8-(2-phenoxyethoxy)caffeine; reversible inhibition; selective inhibition; structure-activity relationship